Analisis Pengaruh Indikator Terhadap Keberlanjutan Energi di Provinsi Banten - Andri Zulkarnaini; Leonard Lisapaly; Martua Manik; Rudy Yulianto (G-Tech: Jurnal Teknologi Terapan, 2024)
The importance of energy sustainability in Banten Province must be able to fulfil national energy needs in the future. In this case, making the right decision by energy policy makers and energy experts is a must to achieve this goal. Determination of appropriate, effective and relevant energy indicators is needed to improve and enhance the energy sustainability infrastructure as targeted. The purpose of this research is to present new indicators, investigate and develop various indicators that can be used to improve the sustainable energy development index. Seven indicators were selected for in-depth study, related data for each indicator were collected and analysed using comprehensive analysis method. The results of the conceptual analysis show that policy makers and energy experts should have careful planning to implement the established policies by taking into account the balance of the economy, security of energy supply, and preservation of environmental functions, then the top priority of energy development should adopt the principle of environmentally friendly energy.